Polyamine oxidase activity in blood of children infected with thalassemia in Nineveh governorate - Lana Mansour (مجلة التربية والعلم, 2010)
Abstract Polyamine Oxidase (PAO) )EC: 1.5.3.11( activity in serum of (20) cases of Untreated Thalaessamia, aged Six month to one year of both sexes, and (50) children of treated thalassmia, aged 1.5 to 15 years of Both sexes, and (50) normal children, aged six month to 15 years of both sexes also. In the Present investigation the activity of PAO in blood of untreated and treated cases of thalaessmia was compared with in normal children. The results obtained showed PAO specific activity in haemolysate of red blood corpuselus and serum of untreated children was (0.641  0.320) and (0.101  0.005) respectively, while the mean value of activity in treated children was (7.574  0.929) and (1.900  0.648) in the haemolysate and serum respectively Compared with (3.019  0.2041) and (0.352  0.120) in the haemolysate and serum respectively, statistical analysis showed a significant of activity in normal child, treated and untreated children (P  0.05), there is no sex significant in (PAO) activity, while age have significant effect in (PAO) activity.